Question Number 131302 by EDWIN88 last updated on 03/Feb/21
$${Given}\:\mathrm{sin}\:\left(\frac{\pi}{\mathrm{6}}+\mathrm{tan}^{−\mathrm{1}} \left({x}\right)\right)=\:\frac{\mathrm{13}}{\mathrm{14}} \\ $$$$\:{If}\:\mathrm{tan}^{−\mathrm{1}} \left({x}\right)=\:\mathrm{tan}^{−\mathrm{1}} \left(\frac{{a}\sqrt{\mathrm{3}}}{{b}}\right)\:{then}\: \\ $$$$\:\frac{{a}+{b}}{\mathrm{2}}\:=?\: \\ $$
Answered by mr W last updated on 03/Feb/21
$${t}=\mathrm{tan}^{−\mathrm{1}} {x}\:<\frac{\pi}{\mathrm{3}}\:! \\ $$$$\mathrm{sin}\:\left(\frac{\pi}{\mathrm{6}}+{t}\right)=\frac{\mathrm{13}}{\mathrm{14}} \\ $$$$\frac{\mathrm{1}}{\mathrm{2}}\mathrm{cos}\:{t}+\frac{\sqrt{\mathrm{3}}}{\mathrm{2}}\mathrm{sin}\:{t}=\frac{\mathrm{13}}{\mathrm{14}} \\ $$$$\mathrm{cos}\:{t}+\sqrt{\mathrm{3}}\mathrm{sin}\:{t}=\frac{\mathrm{13}}{\mathrm{7}} \\ $$$${u}=\mathrm{cos}\:{t} \\ $$$$\sqrt{\mathrm{3}\left(\mathrm{1}−{u}^{\mathrm{2}} \right)}=\frac{\mathrm{13}}{\mathrm{7}}−{u} \\ $$$$\mathrm{3}\left(\mathrm{1}−{u}^{\mathrm{2}} \right)=\frac{\mathrm{169}}{\mathrm{49}}+{u}^{\mathrm{2}} −\frac{\mathrm{26}}{\mathrm{7}}{u} \\ $$$$\mathrm{2}{u}^{\mathrm{2}} −\frac{\mathrm{13}}{\mathrm{7}}{u}+\frac{\mathrm{11}}{\mathrm{49}}=\mathrm{0} \\ $$$${u}=\frac{\mathrm{1}}{\mathrm{4}}\left(\frac{\mathrm{13}\pm\mathrm{9}}{\mathrm{7}}\right)=\frac{\mathrm{11}}{\mathrm{14}},\:\frac{\mathrm{1}}{\mathrm{7}} \\ $$$$\mathrm{tan}\:{t}=\sqrt{\frac{\mathrm{1}}{\mathrm{cos}^{\mathrm{2}} \:{t}}−\mathrm{1}}=\frac{\mathrm{5}\sqrt{\mathrm{3}}}{\mathrm{11}},\:\mathrm{4}\sqrt{\mathrm{3}}>\sqrt{\mathrm{3}}\:!\:{rejected} \\ $$$$\Rightarrow{t}=\mathrm{tan}^{−\mathrm{1}} \frac{\mathrm{5}\sqrt{\mathrm{3}}}{\mathrm{11}} \\ $$$$\mathrm{tan}^{−\mathrm{1}} {x}={t}=\mathrm{tan}^{−\mathrm{1}} \frac{\mathrm{5}\sqrt{\mathrm{3}}}{\mathrm{11}} \\ $$$$\Rightarrow{a}=\mathrm{5},\:{b}=\mathrm{11} \\ $$$$\Rightarrow\frac{{a}+{b}}{\mathrm{2}}=\mathrm{8} \\ $$